Ultrasonic testing of structural defects in honeycomb composite specimens - Aloyscieus, S (Nanyang Technological University, 2024)
Honeycomb composite structures plays a pivotal role in many industries due to their exceptional strength to weight properties. The detection of defects within these structures are critical to maintain structure integrity of the component. This study explores the capabilities of Non-Destructive Testing techniques like Ultrasonic Testing, specifically pulse echo and through transmission technique, in detecting and characterizing defects within honeycomb specimens. The primary objective is to assess the effectiveness and accuracy of the ultrasonic testing methods, with a focus on deliberate defects of varying positions, shapes, and sizes. Two fabricated specimens are utilized, with different face sheets – aluminium and carbon fiber-reinforced polymer – to aluminium honeycomb core to enable a comprehensive evaluation of the UT techniques. Results reveals that through transmission technique is superior in terms of defect detection accuracy compared to pulse echo. Specimen B, with an aluminium-to- aluminium interface outperforms specimen A in both techniques, emphasising the influence of the transmission medium on accuracy. Furthermore, contrary to prior research, pulse echo technique successfully detects cuts in the honeycomb core as well as defects which are on the opposite side of the specimen. These findings provide valuable insights for improving inspection techniques and practices in industries relying on honeycomb structures.